MEASURING PASSENGER SATISFACTION LEVEL USING GAP SCORE ANALYSIS AND IMPORTANCE PERFORMANCE ANALYSIS AT TRAIN STATION - Filscha Nurprihatin; Yosua Budi Kurniawan; Glisina Dwinoor Rembulan (Universitas Bunda Mulia, 2022)
The government continues to promote public transportation so that people living in Jakarta can switch from private transportation to public transportation to reduce congestion. Rail transportation is one of the widely used modes of transportation by people when they want to travel. However, at the beginning of 2020, there was a decline in passengers and there were several regulations for traveling, this was useful to suppress the level of spread of the Coronavirus Disease 2019 (COVID-19). Regulations and conditions for passengers who will travel by train must comply with several things, such as being obliged to follow the instructions and rules that already exist at the train station, conducting a rapid test, and having proof that the results must be negative. This research is conducted using the service quality method and Importance-Performance Analysis (IPA). The level of service provided by the station still must be improved to maintain the satisfaction of the passengers, because the gap scores still have a negative value. Several things cause the passengers to still not feel satisfied with some services. Eight attributes have a gap value greater than the average gap obtained. The company should continue to pay attention to the comfort and satisfaction of passengers when using train services to travel somewhere. Especially at the service level related to rapid tests, more attention can be given because there are so many passengers who will carry out rapid tests in the station area.